Obesity Uncovers the Presence of Inflammatory Lung Macrophage Subsets With an Adipose Tissue Transcriptomic Signature in Influenza Virus Infection - Alarcon, Pablo C; Ulanowicz, Cassidy J; Damen, Michelle S M A; Eom, John; Sawada, Keisuke; Chung, Hak; Alahakoon, Tara; Oates, Jarren R; Wayland, Jennifer L; Stankiewicz, Traci E; Moreno-Fernandez, Maria E; Zacharias, William J; et al. (The Journal of infectious diseases, 2025)
Obesity is an independent risk factor for increased disease severity during influenza A virus (IAV) infection. White adipose tissue (WAT) inflammation promotes disease pathogenesis in obesity. Whether obesity modifies lung and WAT immune cells to amplify influenza severity is unknown. We show that obesity establishes a proinflammatory transcriptome in lung immune cells that is augmented during IAV infection and that IAV infection changes WAT immune cell milieu in obesity. Notably, a decrease in WAT macrophages (ATM) inversely correlates with an increase in infiltrating lung macrophages in obese IAV-infected mice. Further analyses of lung immune cell uncovered a macrophage subset that shares a transcriptomic signature with inflammatory ATMs. Importantly, adoptive transfer of ATMs from obese mice into lean IAV infected mice promotes host immune cell infiltration to the lungs. These findings suggest that, in an obese state, ATMs may exacerbate the inflammatory milieu important in pathologic responses to IAV infection.